Development of Life Management in Study of Adolescent Students Test - หุ่นแสน, สรรเสริญ; พจนาอารีย์วงศ์, จิราภรณ์ (Ratchaphruek Journal, 2019)
The objectives of this research were to develop life management in study of adolescent students test and measure the discrimination validity and reliability. The samples were 560 adolescent students in the upper secondary school level. They were selected by Stratified Random Sampling. The instruments used in data analysis were based on Index of Item-objective congruence, Pearson product moment correlation, and Cronbach’s alpha coefficient. The results of this research were; 1) the life management in study of adolescent students test was designed as a five-level scale. Essentially, most real, actually modesty, a little real, not at all. There were 30 questions and consisted of three factors; Selection, Optimization, and Compensation,2) the life management in study of adolescent students test had item discrimination index, which were in the range of .29-.74, the construct validity correlation coefficients between each component; and between each component and total score were .43-.66 and .66-.75respectively, the reliability of the test was .89.